E-Finance Information Technology Governance Analysis Using the Domain MEA COBIT 5 Frameworks in the Regional Financial Agency of Salatiga City - Delvy Alva Pattiasina; Yani Rahardja; Melkior N.N Sitokdana (TEPIAN, 2020)
Utilization of Information Technology (IT) is able to produce good government management. The implementation of E-Finance continues to be developed by the Regional Finance Agency "BKD" in helping people make online tax payments and management through the website. COBIT 5 as a framework that focuses on control, not execution, so that it can optimize IT utilization, as well as ensure service delivery and measure against what can be done to answer future needs. This research focuses on one of the COBIT 5 domains in it, namely Monitor, Evaluate, and Assess (MEA). By utilizing the Domain MEA COBIT 5. The results of the calculation of the maturity level of IT management at Regional Finance Agency of Salatiga City have reached level 2 in the Capability Model table, namely Managed Process with the results of the gap analysis of each process is the GAP from MEA01 of 2.19, in MEA02 with GAP owned by 2.56 and MEA03 has a GAP of 2.46. In each process, the MEA domain from MEA01, MEA02, and MEA03 has been conducted, monitored, and evaluated on IT performance with reference to organizational policies (Niemann, 2010).